PREDICTION OF CONVERSION OF LAPAROSCOPIC CHOLECYSTECTOMY TO OPEN CHOLECYSTECTOMY USING A PREOPERATIVE SCORING SYSTEM - KOLA CHANDRASEKHAR REDDY; SASIDHARA RAO A; JAYADURGA CHALAMALASETTY; PRERANA RAJU GUDIMETLA; SRIDHAR PUNYAPU; RAVI GANJI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectiveof the study is To use the Risk Score to predict conversion of laparoscopic cholecystectomy to open cholecystectomy and to evaluate whether this scoring method can be used routinely. Methods : A Prospective Observational Clinical study conducted in 106 cases who underwent elective laparoscopic cholecystectomy were analysed prospectively both preoperatively and postoperatively using the scoring system. Results: A total of 106 patients were studied. The highest incidence of gallstone in present series is in the age group of 30 to 40 years. The gender ratio (Male: Female) is 1: 2.3. Of the 106 patients, all had cholelithiasis, 6 patients had GB wall thickening, 1 had impacted stone and none had peri-cholecystic collection. In the present study, Age >50, BMI >;27.5, H/O prior hospitalization for acute cholecystitis, wall thickening, vomiting’s, were significant predictors of difficult laparoscopic cholecystectomy. The conversion rate from laparoscopic cholecystectomy to open cholecystectomy was 12.3%. Of the total 19 cases falling under moderate risk 12 were converted to open cholecystectomy. Rest was managed and completed by laparoscopically. Only one case in the mild risk group was converted to open, reason being the short cystic duct. The most common intraoperative reason for conversion was adhesions in 10 patients, followed by frozen calots, short cystic duct and Mirizzi syndrome. The positive predictive value for easy prediction was 100%. Conclusion: The scoring system used has got better significance in prediction of conversion from lap to open cholecystectomy.